The private cost of long-term care in Canada: Where you live matters - Natasha Fernandes; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2010)
Canadians expect the same access to health care whether they are rich or poor, and wherever they live, often without direct charge at the point of service. However, we find that the private cost of long-term care differs greatly across the country, and within provinces, we find substantial variation, depending on income level, marital status, and, in Quebec alone, on assets owned. A non-married person with average income would pay more than twice as much in the Atlantic provinces as in Quebec, while a couple with one in care would pay almost four times as much in Newfoundland as in Alberta.
Keywords: I11; J14; 330; long-term care; private cost; Alte Menschen; Einkommen; Pflegedienst; Kosten; Kanada